Progress towards flowering of faba bean (Vicia faba L.) is more than photothermal. (20th February 2017) - Lizarazo, C. I.; Isotalo, J.; Lindfors, A. V.; Stoddard, F. L.
Abstract: Predicting and understanding the progress towards flowering in faba bean are important to achieve the adaptation and high productivity of the crop under varying environmental conditions. Traditional controlled‐environment experiments showed that the rate of progress towards flowering was dependent mainly on photoperiod and temperature. Here, we highlight the need to include measures of solar radiation and water deficit in order to achieve an adequate model for field conditions. The improved model was assessed in two steps: first with a "basic" model across all 20 cultivars and then with an "extended" model that included terms to fit exceptional cultivars. The two new parameters were necessary to achieve an acceptable fit of progress towards flowering and clearly separated two cultivars, "Kontu" and "Witkiem Manita, " that were significantly quicker to flower than the other 18, which fit a single line. As the regression coefficients of the two exceptional cultivars differed only in intercept, not slope, we conclude that flowering responses to day length, temperature, solar radiation and drought stresses were consistent in this set of germplasm and that the two cultivars differed in earliness " per se ." Growth‐chamber experiments added information about differing ceiling temperatures for progress to flowering in four cultivars and different sensitivities to supraoptimal temperatures.